Time-Varying Impacts of Financial Stress on Energy-Related Uncertainty - Khodjaniyazov, Nurbek; Mirkhoshimova, Mokhirakhon; Kalandarov, Feruz; Matyokubova, Dilfuza; Utegenova, Sarbinaz; Makhmudov, Samariddin; Khudayberganov, Mansurbek (International Journal of Energy Economics and Policy, 2025)
In literature, studies address the relationship between financial and energy markets. In this context, there are a lot of works which examine the impact of financial markets on energy markets. However, there are not any research undertaken to explore the effect of financial stress index (FSI) on energy-related uncertainty index (EUI). Therefore, this work assesses this relation in the case of US with time-varying parameter vector autoregression (TVP-VAR) model, using monthly data from Quarter 1 1996 to Quarter 3 2022 in the United States (US). The findings reveal that time-varying impacts of FSI on EUI is positive and significant, validating theoretical linkage.